Variable Bragg x-ray beam splitters - L. T. Powers; M. Z. Kwasniewski; S. M. Durbin (AIP Advances)
Beam splitters are utilized in a variety of advanced x-ray instruments and are essential for extending quantum optics techniques to x rays. A new fabrication method has produced thinned Bragg diffracting silicon devices with variable reflectivity and transmission coefficients and negligible absorption losses. Diffraction measurements confirm that silicon continues to exhibit perfect crystal diffraction even for thicknesses below two microns. Devices are machined from standard wafers, with the thinned regions contained within the robust frame of an unperturbed crystal for ease of handling.